Gene Expression Analysis of Toll-Like Receptor Pathways in Heterophils from Genetic Chicken Lines that Differ in Their Susceptibility to Salmonella enteritidis - Kogut, Michael; Chiang, Hsin-I; Swaggerty, Christi; Zhou, Huaijun (Frontiers in Genetics, 2012)
Previously conducted studies using two chicken lines (A and B) show that line A birds have increased resistance to a number of bacterial and protozoan challenges and that heterophils isolated from line A birds are functionally more responsive. Furthermore, when stimulated with toll-like receptor (TLR) agonists, heterophils from line A expressed a totally different cytokine and chemokine mRNA expression pattern than heterophils from line B. A large-scale gene expression profile using an Agilent 44K microarray on heterophils isolated from line A and line B also revealed significantly differential expression in many immune-related genes following Salmonella enteritidis (SE) stimulation, which included genes involved in the TLR pathway. Therefore, we hypothesize the differences between the lines result from distinctive TLR pathway signaling cascades that mediate heterophil function and, thus, innate immune responsiveness to SE. Using quantitative RT-PCR on mRNA from heterophils isolated from control and SE-stimulated heterophils of each line, we profiled the expression of all chicken homologous genes identified in a reference TLR pathway. Several differentially expressed genes found were involved in the TLR-induced My88-dependent pathway, showing higher gene expression in line A than line B heterophils following SE stimulation. These genes included the toll-like receptor genes TLR4, TLR15, TLR21, MD2, the adaptor proteins toll-interleukin 1 receptor domain containing adaptor protein (TIRAP), Tumor necrosis factor-receptor associated factor 3 (TRAF3), the IκB kinases TGF-β-activating kinase 1 (TAK1), IKKε and IKKα, the transcription factors NFkB2 and interferon regulatory factor 7 (IRF7), phosphoinositol-3 kinase (PI-3K), and the mitogen-activated protein kinase (MAPK) p38. These results indicate that higher expression of TLR signaling activation of both MyD88-dependent and TRIF-dependent pathways are more beneficial to avian heterophil-mediated innate immunity and